Marriage, Property and Conversion among the Zoroastrians: From Late Sasanian to Islamic Iran* - Daryaee, Touraj (Journal of Persianate studies, 2013)
Abstract This essay discusses the impact of xwēdōdah or consanguine marriages, sanctioned by the Zoroastrian tradition on the population during a time of religious dialogue, and proselytizing in Ērānšahr (600-800 CE). I believe that advocacy for such a type of marriage was intensified in particular periods in Iranian history, namely the third century, when the Manichaeans challenged Zoroastrianism; and more importantly in the 6th century when Christianity became a major threat; and finally in the eighth and the ninth centuries when state support for Zoroastrianism had collapsed and the Muslims were gaining numbers and becoming the new elite. It is asserted here that xwēdōdah had a practical purpose, which was to keep wealth within the family and the community at a time when conversion threatened the survival of Zoroastrianism.